Application of special exercises to develop the fixation time and the skills of forehand and backhand groundstrokes in tennis players - Saif Abbas Jihad Al-Rubaye; Murtadha Sulttan Hussein (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.